Blended Islamic Finance Sebagai Strategi Pembiayaan Pembangunan Daerah Inklusif di Indonesia: Analisis Kualitatif Berbasis Data Sekunder - Siti Aminah; M.F. Hidayatullah; Abdul Wadud Nafis (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2026)
This study aims to analyze the role of blended Islamic finance as a financing strategy for inclusive and sustainable regional development in Indonesia. This study is motivated by limited regional fiscal capacity and the need for alternative financing sources that can support development without increasing dependence on debt-based financing. The study used a qualitative approach with a library research method based on secondary data obtained from scientific journals, books, institutional reports, regulations, and publications related to the 2021–2026 period. Data analysis was conducted through the stages of data reduction, data presentation, and descriptive-analytical conclusion drawing. The results show that blended Islamic finance, which integrates Islamic social financial instruments such as zakat and waqf with Sharia commercial financial instruments such as sukuk and Sharia microfinance, can create a more inclusive, equitable, and sustainable financing model. The application of the risk-sharing principle enables a more proportional distribution of risks and benefits, thus supporting sustainable regional development. Furthermore, the integration of these instruments contributes to infrastructure financing, MSME empowerment, poverty reduction, and improved community welfare. This study concludes that blended Islamic finance has great potential as an alternative financing for regional development that supports economic growth while realizing social justice, although its implementation still faces challenges in the form of limited regulations, low Islamic financial literacy, and weak coordination between managing institutions.